A model for leveraging social learning technologies in corporate environments - Yap, Robin; Robben, Joost (Proceedings of the International Conference on Networked Learning, 2010)
How are you leveraging your social learning technologies to engage your employees? This research-in-progress paper will provide a model to assist in determining how social learning technologies in the workplace can be leveraged to engage, build relationships, and enhance the learning of individuals in corporate environments. An exploration of how trust and human resource development theories can contribute to the development of social capital in organizations and the web technologies that bind them frames this model. Two concurrent case studies in Canada and in the Netherlands are currently being conducted to identify the viability of this model in the workplace.